2007
DOI: 10.1111/j.1570-7458.2007.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent effects of aerial applications of disparlure on gypsy moth: trap catch and mating success

Abstract: In forest plots treated aerially with a plastic laminated flake formulation (Disrupt® II) of the gypsy moth sex pheromone disparlure to disrupt gypsy moth, Lymantria dispar (L.) (Lepidoptera: Lymantriidae), mating was monitored the year of treatment and 1–2 years after treatment to determine the effects of the treatment on suppression of trap catch and mating success. In the year of treatment, there was a greater than 95% reduction in trap catch and a greater than 98% reduction in mating success compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…1), even though past research has consistently shown that mating success declines signiÞcantly in plots treated with mating disruption related to untreated control plots (Tcheslavskaia et al 2005;Thorpe et al 2006Thorpe et al , 2007Onufrieva et al 2008Onufrieva et al , 2010. One reason for the lack of a difference could be the overall rarity at which we observed low-fertilized egg masses, making it challenging to detect a signiÞcant difference.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…1), even though past research has consistently shown that mating success declines signiÞcantly in plots treated with mating disruption related to untreated control plots (Tcheslavskaia et al 2005;Thorpe et al 2006Thorpe et al , 2007Onufrieva et al 2008Onufrieva et al , 2010. One reason for the lack of a difference could be the overall rarity at which we observed low-fertilized egg masses, making it challenging to detect a signiÞcant difference.…”
Section: Discussioncontrasting
confidence: 58%
“…Field studies were conducted each year from 2001 to 2007 and 2009 at sites in the AppomattoxBuckingham State Forest, Cumberland State Forest, and Goshen Wildlife Management Area (all in Virginia). These studies were designed to measure the effect of mating disruption tactics, such as product formulation and dose, against L. dispar populations (Tcheslavskaia et al 2005;Thorpe et al 2006Thorpe et al , 2007Onufrieva et al 2008Onufrieva et al , 2010. Mating disruption products were Hercon Disrupt II (Gelva 2333, Solutia Inc., SpringÞeld, MA), SPLAT GM (ISCA Technologies, Riverside, CA), and 3M MEC-GM Sprayable Pheromone (3M Canada Co., London, ON, Canada) applied at various doses, from 15 to 37 g/ha.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pest suppression tactics can also interfere with surveillance programs to detect, delimit, or monitor the pest population. Pheromone-baited traps, for example, can be silenced by widespread application of pheromone applied for mating disruption (Thorpe et al 2007), a critical concern when trap catch data are needed for decision-making . While it is also possible that these traps are not silenced through mating disruption but rather indicate treatment efÞcacy, poorly conceived combinations are still counterproductive and the possible interactions need to be examined carefully.…”
Section: Quality Of Interaction Examplesmentioning
confidence: 99%
“…In 2014, the experimental plots treated in 2013 were monitored to evaluate gypsy moth mating disruption one year after the treatment application given that past research demonstrated persistence of mating disruption tactics one year after treatment (Onufrieva et al, ; Thorpe et al, ). Male moths were released once a week for 10 weeks.…”
Section: Methodsmentioning
confidence: 99%